Central nervous system alterations caused by infection with the human respiratory syncytial virus. (14th October 2014) - Bohmwald, Karen; Espinoza, Janyra A.; González, Pablo A.; Bueno, Susan M.; Riedel, Claudia A.; Kalergis, Alexis M.
SUMMARY Worldwide, the human respiratory syncytial virus (hRSV) is the leading cause of infant hospitalization because of acute respiratory tract infections, including severe bronchiolitis and pneumonia. Despite intense research, to date there is neither vaccine nor treatment available to control hRSV disease burden globally. After infection, an incubation period of 3–5 days is usually followed by symptoms, such as cough and low‐grade fever. However, hRSV infection can also produce a larger variety of symptoms, some of which relate to the individual's age at infection. Indeed, infants can display severe symptoms, such as dyspnea and chest wall retractions. Upon examination, crackles and wheezes are also common features that suggest infection by hRSV. Additionally, infection in infants younger than 1 year is associated with several non‐specific symptoms, such as failure to thrive, periodic breathing or apnea, and feeding difficulties that usually require hospitalization. Recently, neurological symptoms have also been associated with hRSV respiratory infection and include seizures, central apnea, lethargy, feeding or swallowing difficulties, abnormalities in muscle tone, strabismus, abnormalities in the CSF, and encephalopathy. Here, we discuss recent findings linking the neurological, extrapulmonary effects of hRSV with infection and functional impairment of the CNS. Copyright © 2014 John Wiley & Sons, Ltd.